Imagined states : law and literature in Nigeria, 1900-1966 - Baxter, Katherine Isobel, 1976- (Edinburgh : Edinburgh University Press, 2019)
Examines representations of the law in colonial and postcolonial fiction from and about Nigeria Imagined States examines representations of the law in British and Nigerian high-brow, middle-brow and popular fiction and journalism. Drawing on a rich range of examples, the book focuses on the imaginative role that the state of exception played in the application of indirect rule during British colonialism and in the legal machinations of the postcolonial state. It reads works by Chinua Achebe, Joyce Cary, Cyprian Ekwensi and Edgar Wallace, together with a range of Nigerian market literature and journalism.
Introduction: literature, imagination and the state of exception -- 'Natural justice, equity and good conscience': history, politics and law in Nigeria, 1900-1966 -- 'I am the law': district commissioner fiction and the state of exception -- 'Seeking a legal form': Joyce Cary's Mister Johnson -- 'Beast of no nation': bribery, corruption and the late colonial administration in no longer at ease -- 'Written in the interest of the people': representing the law in Cyprian Ekwensi and market literature -- 'Sensational coverage of a sensational trial': treason, journalism and the state -- Violence and the law in a man of the people -- Conclusion: imagined states -- Bibliography -- Index.
Includes bibliographical references and index.
JSTOR
Keywords: Nigerian literature (English) -- History and criticism; Law in literature; Littérature nigériane (anglaise) -- Histoire et critique; Droit dans la littérature.; Law in literature; Nigerian literature (English); Criticism, interpretation, etc